2016
DOI: 10.1016/j.ajpath.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cell Transplantation in Mice for Elucidating Monocyte/Macrophage Biology and for Potential in Cell or Gene Therapy

Abstract: Kupffer cells (KC) play major roles in immunity and tissue injury or repair. Because recapitulation of KC biology and function within liver will allow superior insights into their functional repertoire, we studied the efficacy of the cell transplantation approach for this purpose. Mouse KC were isolated from donor livers, characterized, and transplanted into syngeneic recipients. To promote cell engraftment through impairments in native KC, recipients were preconditioned with gadolinium chloride. The targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…18 More recently, Merin et al reported that transplanted yolk sacderived Kupffer cells (KCs) exhibited beneficial effects on acetaminophen hepatotoxicity or hepatic ischemia-reperfusion injury. 19 These studies are consistent with the idea that infusion of M1-or M2-polarized macrophages or macrophages with different origin (such as the hepatic resident KCs) might have a different therapeutic output compared to taking the macrophage populations as a whole.…”
supporting
confidence: 83%
“…18 More recently, Merin et al reported that transplanted yolk sacderived Kupffer cells (KCs) exhibited beneficial effects on acetaminophen hepatotoxicity or hepatic ischemia-reperfusion injury. 19 These studies are consistent with the idea that infusion of M1-or M2-polarized macrophages or macrophages with different origin (such as the hepatic resident KCs) might have a different therapeutic output compared to taking the macrophage populations as a whole.…”
supporting
confidence: 83%
“…Although gene therapy is advancing for hemophilia, cell transplantation will be significant for complex coagulation factor deficiencies, repair of vascular and tissue damage, as well as tissue engineering and neoorganogenesis. As multiple cell types may be transplanted simultaneously to reconstitute the liver, including hepatocytes, LSEC, KC, and HSC, 12,55 cell interactions may be studied in vivo. These studies of cell interactions will be advanced by efficient engraftment and proliferation of co-transplanted cells with the mechanism of ET A/B antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…As engraftment in liver of transplanted KC is inefficient and these do not proliferate, their presence was inconsequential. 12 ET A/B receptor antagonism by BOS and time-to-transplantation…”
Section: Lsec Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, cultured hepatocytes begin to dedifferentiate and lose their polarity over a short time. An additional key factor that has limited the application of hepatocyte transplantation is the significant cell loss posttransplantation [266,267,[273][274][275][276][277][278][279]. Without immunosuppressive drugs, transplanted allogeneic hepatocytes survive for only 7 to 10 days [258,267,280].…”
Section: Figure 15 Ldlr-mediated Endocytosis Is Restored In Correctementioning
confidence: 99%